(untitled) (Experimental biology, 2021)
The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) was finally agreed in Washington DC, on March 3 1973. It was ratified by the Parliament of Bulgaria in 1991 and published in 1992. The study presents characteristics of the systematic structure and ecological and biological characteristics of Bulgarian flora plants, included in Appendix II of the Convention. According to the Convention, 77 species belonging to 29 genera and 4 families of Bulgarian flora are protected. The intraspecific diversity includes 18 subspecies, varieties and two forms. The plants are classified according to biological types, life form and floristic elements following Walter. Also, information on the distribution of these species in Bulgaria and their ecological groups are presented. The conservation importance of the species is analyzed in the national and international context. Full systematic list of the species of Bulgarian flora, protected by Appendix II of the CITES is presented. Key words: Bulgaria, flora, CITES.